Coronary Access and Percutaneous Coronary Intervention Up to 3 Years After Transcatheter Aortic Valve Implantation With a Balloon-Expandable Valve. (July 2020) - Tarantini, Giuseppe; Nai Fovino, Luca; Le Prince, Pascal; Darremont, Olivier; Urena, Marina; Bartorelli, Antonio L.; Vincent, Flavien; Hovorka, Tomas; Alcalá Navarro, Yasmina; Dumonteil, Nicolas; Ohlmann, Patrick; Wendler, Olaf
Abstract : Background: Coronary artery disease and aortic stenosis often coexist. Transcatheter aortic valve implantation (TAVI) has emerged as a valid therapeutic option for younger, lower-risk patients who may eventually require coronary artery disease treatment. Thus, post-TAVI coronary access (CA) and percutaneous coronary intervention are expected to increase. The purpose of this study was to retrospectively evaluate patients who were enrolled in the SOURCE 3 (SAPIEN 3 Aortic Bioprosthesis European Outcome) European registry for treatment with the balloon-expandable SAPIEN 3 transcatheter heart valve and underwent CA with or without percutaneous coronary intervention after TAVI. Methods: Baseline characteristics and clinical outcomes of patients with or without CA up to 3 years after TAVI were compared. A Kaplan-Meier estimate with a univariate model determined the impact of CA on cardiac mortality. Results: Of 1936 TAVI patients (mean age 81.6 years, 52% male), 68 (3.5%) had CA within 3 years (mean 441±332 days) after TAVI. At baseline, the logistic EuroSCORE was similar (20.2% versus 18.3%, P =0.2, CA and non-CA groups, respectively). Higher rates of coronary artery disease (76.5% versus 50.6%, P <0.001), myocardial infarction (20.6% versus 11.5%, P =0.03) and previous coronary artery bypass graft (22.1% versus 11.0%, P =0.01) were present in the CA group. In 100% of patients, CA was successfully achieved. The clinical success of percutaneous coronary intervention was 97.9%. Cardiovascular mortality was numerically higher in patients with CA than in those without CA. Conclusions: In the large SOURCE 3 European registry, CA was needed at 3-year follow-up after TAVI with a balloon-expandable valve in 3.5% of patients and was successful in all patients. The clinical success of percutaneous coronary intervention was 97.9%. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02698956.